Dental aspects of children with Down syndrome - Ambarkova Vesna; Ana Sotirovska Ivkovska; Natasa Stavreva (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Down syndrome (trisomy 21) is the most common autosomal chromosome aberration in human. The incidence of the syndrome varies in 1:700 and 1:1000 live births according to various studies, with 20% of cases. In aborted material proportion is even higher, with 60% of cases. While 20% of cases with Down syndrome are stillborn. In these patients, there is a strong predisposition to cardiovascular disease, seizures [1], leukemia[2,3], infections with hepatitis B virus (especially within institutionalized men)[4], upper respiratory tract infections [5], Alzheimer's disease[6], obesity [7], thyroid diseases [8], cardiac anomalies [9], and obstructive sleep apnea [10,11]. Disruption of the proteostasis network and accumulation of misfolded proteins occur as a result of an abnormality in the number of hromosome 21 [12]. Errors in protein homeostasis could contribute to the observed pathology and decreased cell viability in children with Down syndrome [13].